Peer drug use and adolescent polysubstance use: Do parenting and school factors moderate this association?. (January 2017) - Chan, Gary C.K.; Kelly, Adrian B.; Carroll, Annemaree; Williams, Joanne W.
Abstract: Aims: This study examined the association between peer drug use and adolescent polysubstance use, and investigated if this association was moderated by parenting and/or school factors. Methods: The sample consisted of 9966 participants (mean age = 14.3; 49.34% males) randomly selected from secondary schools in Victoria, Australia. Three 30-day polysubstance use profiles were derived from latent class analysis – no drug use (47.7%), mainly alcohol use (44.1%) and polysubstance use (8.2%). These profiles were then regressed on peer's drug use, family conflict, parental monitoring, parental disapproval of drug use, school commitment, reward for prosocial involvement in school and academic failure, and the interactions between peer's drug use and each of the parenting and school variables. Results: Relative to non-users, peer's drug use was strongly associated with polysubstance use (OR = 30.91, p < 0.001), and this association was moderated by parental disapproval of drug use (OR = 0.46, p < 0.001). This indicated that high level of parental disapproval may mitigate the negative influence of drug using peers. School commitment and parental monitoring were significantly associated with reduced likelihood of polysubstance use ( p < 0.05), but they did not moderate the relationship between peer drug use and adolescent polysubstance use. All analyses were adjusted for key demographic factors such as age, gender, areas of residence, birth place and family affluence. Conclusion: Reinforcing parent disapproval of drug use may be an important strategy in reducing adolescent substance use. Parents may need to be more integrated into mainstream prevention programs. Highlights: Adolescent polysubstance use was strongly associated with peer's drug use. Parental disapproval of drug use was associated with reduced polysubstance use, and mitigated the influence of peers. Other parenting and school factors influenced polysubstance use independent of peer's drug use.